2017
DOI: 10.1093/jxb/erx332
|View full text |Cite
|
Sign up to set email alerts
|

White Leaf and Panicle 2, encoding a PEP-associated protein, is required for chloroplast biogenesis under heat stress in rice

Abstract: WLP2, encoding a PEP-associated protein, and its paralog OsFLN2 can interact with OsTRXz to form a TRX-FLN regulatory module to protect chloroplast development from heat stress in rice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 41 publications
6
54
0
Order By: Relevance
“…5A, we found that all the parameters except intercellular CO 2 concentration (C i ) were reduced in the male sterile lines of S. miltiorrhiza. The results showed that the chloroplast structure was abnormal and the performance of photosynthesis was consistent with other research results [41].…”
Section: Discussionsupporting
confidence: 89%
“…5A, we found that all the parameters except intercellular CO 2 concentration (C i ) were reduced in the male sterile lines of S. miltiorrhiza. The results showed that the chloroplast structure was abnormal and the performance of photosynthesis was consistent with other research results [41].…”
Section: Discussionsupporting
confidence: 89%
“…In this paper, we measured the photosynthetic parameters of S. miltiorrhiza leaves of the male fertile lines and male sterile lines, and found that all the parameters including the net photosynthetic rate (A), transpiration rate (E) and stomatal conductance (g s ) of the male fertile lines were higher than those of the male sterile lines except intercellular CO 2 concentration (C i ) in S. miltiorrhiza ( Figure 5A). The results showed that the chloroplast structure was abnormal and the performance of photosynthesis was consistent with other research results [20]. The results also showed that the net photosynthetic rate was positively correlated with the stomatal conductance, which agrees with the statistical analysis of 14 species [21].…”
Section: Abnormal Development Of Chloroplast Structure In Male Sterilsupporting
confidence: 90%
“…To investigate if plastid transcription was impaired by the mutation of UMPK , the expression of plastid genes was examined in young leaves of six-week-old WT and mutant plants. The genes psaA , psbB , psbC, petB , and rbcL were selected as plastid-encoded RNA polymerase (PEP)-dependent genes (Figure 3a); rpoA , rpoB , rpoC1 , and rpl23 were selected as nucleus-encoded RNA polymerase (NEP)-dependent genes (Figure 3b); atpB , ndhB , and psbE were chosen as both PEP- and NEP-dependent genes (Figure 3c) [23,24,25,26]. The expression of all assayed PEP-dependent genes was significantly lower in the mutant, except for rbcL , which showed no significant difference between the WT and the mutant.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that transcript levels of PEP-dependent genes and NEP-dependent genes in the umpk mutant were significantly reduced and elevated, respectively, compared with WT and the complementation lines. This is a typical plastid gene expression pattern resulting from impaired PEP transcription, which frequently results in abnormal chloroplast development [23,26,32,33,34,35,36,37]. The influence of impaired PEP activity on chloroplast development varied during the development of plants: it was more severe at the early stage and gradually diminished with plant development.…”
Section: Discussionmentioning
confidence: 99%